Checklist of Xylaria Hill ex Schrank (Xylariaceae, Xylariales) in Brazilian Atlantic Forest - Gondim, Nicole Helena De Brito; Maia, Leonor Costa; Melo, Roger Fagner Ribeiro (Phytotaxa, 2025)
Xylaria Hill ex Schrank (Xylariaceae, Xylariales) is characterized by the formation of thick walled perithecia in erect, carbonaceous, usually macroscopic stromata, on dead, lignified plant organs. Most species are saprotrophic, but endophytic, parasitic and insect symbionts are also found. Xylaria is mostly a tropical genus, and here the results of a survey on its occurrence in the Brazilian Atlantic Forest are presented. The genus is well represented in this biome. In addition to the 601 compiled herbaria records, 157 records are added here, totaling 758, which correspond to 71 valid taxa. This study contributed with new records of X. escharoidea and X. ruginosa for Brazil, X. digitata, X. euphorbiicola and X. nigripes, for the Brazilian Northeast; X. allantoidea, X. anisopleura, X. arbuscula, X. comosa, X. curta, X. feejeensis, X. grammica, X. hypoxylon, X. longipes, X. myosurus, X. obovata, X. poitei, X. polymorpha, X. telfairii and X. scruposa constitute for Alagoas. Xylaria cubensis and X. apiculata stood out with the highest number of records in Brazil.